Myanmar Agricultural Performance Survey (Q3 2022): Farm commercialization - Myanmar Agriculture Policy Support Activity (International Food Policy Research Institute, 2022)
This Research Note presents the results from an assessment of farm commercialization in Myanmar after the dry season of 2022. The results are based on data from a phone survey – the Myanmar Agriculture Performance Survey (MAPS) – that was conducted with 5,021 crop farmers in all states/regions of the country in Q3 of 2022. This note assesses the perceived security situation of crop farmers, agricultural input availability and prices, prices of major crops at the farm level, changes in income from crop sales, and overall crop marketing challenges.